Evalu[t]ation of bond strength at asphalt interfaces - Wheat, Maurice (Kansas State University, 2007)
The primary objective of this research project was to evaluate the shear behavior of three asphalt-to-asphalt mix interfaces. To accomplish this objective, a special attachment and loading mechanism was designed and built to facilitate the measurement of the dynamic shear reaction modulus and shear strength of the asphalt-to-asphalt interfaces when shear and normal forces are acting simultaneously and they are proportional. Two tests were conducted on 4-inch diameter cylindrical samples cored from an asphalt concrete pad where three types of asphalt-to- asphalt interfaces were built. For each interface, four tack-coat quantities were sprayed. On each sample, the Dynamic Shear Reaction Modulus test was conducted first. Then the Shear Strength test was conducted until the sample failed in shear at the interface. The experiments suggest that the shear strength of the interface is affected neither by the interface type nor by the tack-coat application rate. However, the dynamic shear reaction modulus was affected by both interface type and by the tack-coat application rate. The lowest moduli were recorded for the interface between two fine graded asphalt mixes. With very few exceptions, the highest moduli were obtained for the tack-coat application rate recommended by the construction specification.
Keywords: asphalt; Engineering, Civil (0543)